Forbidden lessons in a Kabul guesthouse : the true story of a woman who risked everything to bring hope to Afghanistan - Sadeed, Suraya; Lewis, Damien (New York : Voice/Hyperion, 2011)
From her first humanitarian visit to Afghanistan in 1994, Suraya Sadeed has been personally delivering relief and hope to Afghan orphans and refugees, to women and girls in inhuman situations deemed too dangerous for other aid workers or for journalists. Her memoir of these missions is as unconventional as the woman who has lived it. Born the daughter of the governor of Kabul amid beautiful gardens and peace, Suraya fled to the United States with her husband and daughter in the aftermath of the 1979 Soviet invasion. In America, she became a prosperous workaholic, but a personal tragedy led her to question the direction of her life. Now, dedicated to the education and welfare of Afghan women and children, she founded Help the Afghan Children (HTAC) to fund her efforts. Here, she shares her story of passion, courage, and love, painting a complex portrait of Afghanistan and its people that defies every stereotype and invites us all to hope.--From publisher description.
Prologue: Lessons by lamplight -- pt. 1. Finding hope in a lawless Afghanistan (1995) -- Help the Afghan Children -- The beginning -- The camel road -- The devil's flowers -- The edge of darkness -- The widow camp -- City of ghosts -- A promise to Fatima -- pt. 2. Imperfect peace under the Taliban -- The tree of amputations -- It is what it is -- Stoned and flying out here -- The day the Earth turned angry -- Of life and love -- Young enough to wed -- The darkness before the dawn -- Singing with the Taliban -- The kindness of strangers -- pt. 3. Under a hail of American bombs (September 2001-present) -- The day everything changed -- The wrong side of the border -- The boy who killed the American -- Hearts and minds -- Epilogue: Drop by drop a river forms -- Afterword.
Keywords: Sadeed, Suraya; Help the Afghan Children (Organization); Women social reformers -- Afghanistan -- Biography; Social reformers -- Afghanistan -- Biography; Afghan American women -- Biography; Children -- Afghanistan -- Social conditions; Afghan War, 2001- -- Social aspects; Afghanistan -- History -- 1989-2001 -- Biography; Afghanistan -- History -- 2001- -- Biography; Afghanistan -- Social conditions -- 20th century; Afghanistan -- Social conditions -- 21st century